Re‐examining the decadal change of tropical cyclogenesis over the South China Sea around the mid‐1990s. (11th February 2019) - Cao, Xi; Wu, Renguang; Zhan, Yingyu
Abstract : A distinct inter‐decadal increase of tropical cyclone (TC) frequency occurred over the South China Sea (SCS) around the mid‐1990s. Previous studies linked this TC frequency increase to changes in seasonal mean background fields and in the intensity of intra‐seasonal oscillations according to regional and seasonal mean fields. The present study compares the contributions of environmental factors on different timescales to inter‐decadal change of the SCS TC frequency from a local and instantaneous perspective. It is shown that the intra‐seasonal variations of lower‐level vorticity, mid‐level specific humidity, and vertical motion have a dominant contribution to the SCS TC genesis during both 1979–1993 and 1994–2002. The inter‐annual anomalies of sea surface temperature (SST), outgoing longwave radiation (OLR), and vertical motion display an increase of favourable state near TC genesis regions at the mid‐1990s. The intra‐seasonal components of favourable OLR and vertical motion anomalies are larger in the latter period than in the former period. The synoptic components of favourable lower‐level vorticity, vertical wind shear, and mid‐level specific humidity anomalies increase from the former period to the latter period. The present study shows that the contributions of environmental factors to the SCS TC frequency have increased on different timescales around the mid‐1990s. The results suggest that this inter‐decadal increase of TC frequency may include both effects of dynamical‐driven changes and stochastic processes. Abstract : The tropical cyclone (TC) genesis frequency over the South China Sea (SCS) experienced an obvious inter‐decadal increase around the mid‐1990s. The present study compares the contributions of environmental factors on different timescales from a local and instantaneous perspective. The inter‐annual anomalies of SST, OLR, and vertical motion display an increase of favourable state near the TC genesis regions at the mid‐1990s. The intra‐seasonal components of favourable OLR and vertical motion anomalies are larger in the latter period. The synoptic components of favourable vorticity, wind shear, and specific humidity anomalies increase. This inter‐decadal increase of TC frequency may include both effects of dynamical‐driven changes and stochastic processes.